2009
DOI: 10.1111/j.1365-2966.2009.14725.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamical simulations of Galactic fountains - II. Evolution of multiple fountains

Abstract: The ejection of gas out of the disc in late‐type galaxies is related to star formation and is mainly due to the explosion of Type II supernovae (SN II). In a previous paper, we considered the evolution of a single Galactic fountain, that is, a fountain powered by a single SN cluster. Using three‐dimensional hydrodynamical simulations, we studied in detail the fountain flow and its dependence with several factors, such as the Galactic rotation, the distance to the Galactic centre and the presence of a hot gaseo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 44 publications
6
69
1
1
Order By: Relevance
“…This result is consistent with the works of Bregman (1980), Fraternali & Binney (2008) and Melioli et al (2008). Melioli et al (2009) presented results for a multiple fountain model produced by randomly clustered explosions of SNe originating in stellar associations spread over a disk area of 8 kpc 2 . As in the case of a single fountain, the spreading of the SN ejecta back into the disk is not very large.…”
Section: Introductionsupporting
confidence: 80%
“…This result is consistent with the works of Bregman (1980), Fraternali & Binney (2008) and Melioli et al (2008). Melioli et al (2009) presented results for a multiple fountain model produced by randomly clustered explosions of SNe originating in stellar associations spread over a disk area of 8 kpc 2 . As in the case of a single fountain, the spreading of the SN ejecta back into the disk is not very large.…”
Section: Introductionsupporting
confidence: 80%
“…Unlike previous work studying supernova-driven superbubbles in three dimensions (Melioli et al 2008(Melioli et al , 2009, in this work we have not taken into account galactic shear or density stratifi- cation, ingredients that these authors have shown to be important in the evolution of the superbubbles as for the study of the overall dynamics of the ISM gas. The simulations presented here rather focus on the study of much smaller spatial and temporal scales.…”
Section: Summary and Discussionmentioning
confidence: 98%
“…In particular, galactic fountains should not affect the outer disk much, because they deliver the ejected material close to the radius where they originate. They are only important for the inner, star-forming parts of the disk (Melioli et al 2008(Melioli et al , 2009). …”
Section: Further Discussionmentioning
confidence: 99%